Establishing Performance Evaluation Model with Queuing Theory in NoC - Tao He; Fucai Chen; Tao Qin (Institute of Advanced Engineering and Science, 2013)
The transmission delay is an important index of the system performance of NoC (Network on Chip). Although the method of simulation-based can get accurate transmission delay, the simulation requires time consuming and a large number of test vectors. Especially in the study of some algorithms, such as mapping algorithms, buffer allocation algorithm, the simulation method is not applicable. To solve the above problems, the paper uses queuing theory to study the establishment of a NoC delay model. The model considers the limited buffer of routing unit and virtual channel technology for network transmission delay and proposes solving algorithm of the delay model based on reverse deduction method. The simulation shows that this model used to analyze the application-specific data transmission delay has smaller average error (reduced by 8%) and higher evaluation efficiency (increased by more than 30 times), which provide designers an efficient method of performance evaluation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3395